FUNGSI PENGAJIAN DAN MUJĀHADAH KAMIS WAGE BAGI KOMUNITAS PESANTREN SUNAN PANDANARAN, SLEMAN, YOGYAKARTA - Mohamad Yahya (Jurnal Living Hadis, 2016)
This article is part of anthropological research about Mujāhadah Kemis Wage in Pesantren Sunan Pandanaran, Sleman Regency, Yogyakarta. Having used participatory technic, interview, observation, as well as documentation data, this research benefited fungsionalisme Bronislaw Malinowski theory for both descripting and analyzing the data. Part of research result are the form of Mujāhadah kamis wage that consist of: (1) khatm al-Qur’ān (2) khatm al- Qur’ān prayer, (3) theological sermons, (4) recitation of asmaul husna, (5) recitation of ratībul ḥaddād, (6) recitation of ‘ibādallah, (7) as well commemoration of ṣalawat during public endorsing. While according to fungcionalism point of view, this public ritual congregation entails  several  functions  spread  from religious dimension, to education, socio-political, up to sectarian ideology.